WAS BORGES A MISOGYNIST? THE CONSTRUCTION OF MASCULINITY AND THE CRITIQUE OF BINARY THOUGHT IN SOME OF THE WORKS OF JORGE LUIS BORGES (Andamios, Revista de Investigación Social, 2008)
This article starts with a discussion of Borges’ alleged misogyny to analyze several works by him from the point of view of the construction of masculinities. Then it explores the relations between Borges’ work and the destabilization of binary systems of thought discussed by Foucault and later taken by Judith Butler as a point of departure of her critique of gender binarism
Keywords: Borges; gender; masculinities; literary criticism